2018
DOI: 10.1038/s41395-018-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Markers (ALBI and APRI) Predict Pregnancy Outcomes in Women With Chronic Liver Disease

Abstract: Most women with cirrhosis who conceived achieved a successful pregnancy outcome. ALBI and APRI scores can prognosticate pregnancy outcomes in women with CLD. Preconception counseling by a hepatologist or specialist obstetrician improved patient care in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…In recent years, the combined analysis of liver enzymes and platelet counts has provided important information regarding the role of new biomarkers in predicting neoplastic and infectious disease severity [47, 48]. One of these biomarkers, the APRI, has been widely studied as a minimally invasive marker of fibrosis and inflammation in hepatic disease [49, 50]. The APRI has also proven useful in predicting the severity of acute and systemic diseases such as dengue [19] and HELLP syndrome [51].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the combined analysis of liver enzymes and platelet counts has provided important information regarding the role of new biomarkers in predicting neoplastic and infectious disease severity [47, 48]. One of these biomarkers, the APRI, has been widely studied as a minimally invasive marker of fibrosis and inflammation in hepatic disease [49, 50]. The APRI has also proven useful in predicting the severity of acute and systemic diseases such as dengue [19] and HELLP syndrome [51].…”
Section: Discussionmentioning
confidence: 99%
“…For active variceal hemorrhage, immediate resuscitation and stabilization of the mother and emergent endoscopic therapy are required. (113,200,(326)(327)(328) Octreotide or somatostatin should also be initiated, but terlipressin should be avoided because it can cause uterine contractions and reduce uterine blood flow (Table 4). Although splanchnic vasoconstriction could reduce placental perfusion and increase risk of placental abruption, (329) comprehensive management of life-threatening variceal bleeding outweighs this theoretical risk.…”
Section: Management Of Gastroesophageal Variceal Bleedingmentioning
confidence: 99%
“…In this cohort, it was also observed that a platelet count before conception of 110 × 10 9 cells/L or less had 78% sensitivity and 89% specificity in predicting the presence of varices on screening endoscopy performed during the second trimester of pregnancy. A more recent investigation of the albumin–bilirubin score and the AST to platelet ratio index determined that these measures in preconception were predictive of live birth and of the ability of pregnancies in women with chronic liver disease and cirrhosis to progress beyond 37 weeks of gestation . Investigators in Germany performed transient elastography on healthy women who were pregnant and on women with pregnancy‐related liver disease (preeclampsia and ICP) .…”
Section: Future Directions: Noninvasive Testing and Prognostic Modelsmentioning
confidence: 99%